PTS - Is it an underestimated form of schooling? Evaluation results of the educational goals of the polytechnic school with the features of school theory in accordance with Fend (Pedagogical Horizons, 2021)
The Austrian education system was expanded in 1962 as a part of the one-year extension of compulsory schooling to nine years by a new, one-year "Polytechnic Course (PL)" form of schooling (Federal Law Journal [BGBL] No. 241 & 242, Compulsory Schooling Act [SchPflG] 1962, School Organisation Act [SchOG] 1962). It was intended as an opportunity to complete this extended period of compulsory schooling combined with the educational goal of vocational preparation. Its legal implementation and commencement proceeded in the school year 1966/67. Soon after the initial phase, acceptance by the student body was restrained and the number of graduates declined over time for various reasons, which resulted in several attempts to make it more attractive, and finally in 1997 (BGBL No. 766/1996) to changing the name to "Polytechnic School (PTS)".In the qualitative research design, internal and external actors were surveyed in group discussions or guided interviews in the Upper Austrian central area and informational materials in the form of curricula and statistics were analysed and compared with the features that the school theorist Fend considered important for Schools (Fend, 2008).The reults show, among other things, that the below-average acceptance of this one-year type of schooling by young people is more likely due to the need for an image correction within society, or to the currently suboptimal social composition of the graduates, especially in urban areas. And that is because the analysis of the overall concept paints a completely workable picture, whereby the overall concept and the educational goals are consistent in terms of preparing for the working world, and its committed implementation has been well executed.
Keywords: Polytechnic School; social composition; image correction; increased attractiveness